Outcome of Conventional Linear Versus Purse String Skin Closure of Intestinal Stoma Reversal (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Stoma closure is one of the most frequently performed surgery. The common complications are surgical site infection (SSI) and poor scar cosmesis. Compared to the conventional linear closure, the pursestring closure technique is expected to have less wound infection, smaller size scar and good patient satisfaction. The aim of this study is to evaluate the feasibility of PSC of stoma site at a tertiary hospital and comparing it with LC of stoma.Materials and methods: This study was performed in the Department of General Surgery, Chittagong Medical College Hospital for a period of one year with a sample size of 72. About 36 subjects were enrolled in each group, Group-A (Linear closure) and Group-B (Purse string closure). Each patient of both group were observed for wound infection, post-operative pain, scar formation, patient satisfaction, and length of post-operative hospital stay.Results: The level of pain according to VAS score was 4 in 36 (100.0%) in Group A and 6(16.7%) in Group B. One third (33.3%) patients had wound infection in Group A and 4(11.1%) in Group B.  The mean duration of hospital stay was 9.72±3.46 days in Group A and 7.97±2.46 days in Group B which is statistically significant (p